SERVICE STRATEGY TOWARDS CUSTOMERS IN AN EFFORT TO INCREASE SALES VOLUME AT MIMISI PASARAYA PEKKAE BRANCH, BARRU DISTRICT - Kasmiah; Lukman, Sri Hardiyanti; Rais, Rahmi; Nur’anisyah (Meraja journal, 2023)
[Full Paper] to pdf Copyright (c) 2023 Meraja journal